Предмет: Алгебра,
автор: Rick111111111
помогите упростить выражение
(3x+y)(x+y)-4y(x-y)
(y-10)(y-2)+(y+4)(y-5)
Ответы
Автор ответа:
0
(3x+y)(x+y)-4y(x-y) (y-10)(y-2)+(y+4)(y-5)=
=3х²+3ху+ух+у²-4у(ху-10х-у²+10у)(у-2)+у²+4у-5у-20=
=3х²+4ху+у²+4у(ху²-10ху-у³+10у²-2ху+20х+у²-20у)+у²-у-20=
=3х²+4ху+у²+4ху³-40ху²-4у⁴+40у³-8ху²+80ху+4у³-20у²+у²-у-20=
=3х²+84ху-18у²+4ху³-48ху²-4у⁴+44у³-у-20
_________________________
(3x+y)(x+y)-4y(x-y)=3х²+3ху+ух+у²-4ху+4у²=3х²+5у²
_____________________________
(y-10)(y-2)+(y+4)(y-5)=у²-10у-2у+20+у²+4у-5у-20=2у²-13у
Rick111111111:
это два разных уравнения
Похожие вопросы
Предмет: Русский язык,
автор: galeevadil0490
Предмет: Қазақ тiлi,
автор: Natalya2013s
Предмет: Математика,
автор: GaBrEl01
Предмет: Математика,
автор: люда198